Chemical structure and dissolution behaviour of CaO and ZnO containing alkali-borosilicate glass. Issue 3 (14th January 2022) - Fisher, Adam J.; Ding, Hao; Rajbhandari, Prashant; Walkley, Brant; Blackburn, Lewis R.; Stennett, Martin C.; Hand, Russell J.; Hyatt, Neil C.; Harrison, Michael T.; Corkhill, Claire L.
Abstract : Altering the CaO to ZnO ratio of alkali borosilicate glass, in favour of ZnO, causes phase separation with hardystonite-like (Ca2 ZnSi2 O7 ) and willemite-like (ZnSi2 O4 ) structures identified. This is concurrent with increased glass durability. Abstract : Within the context of the UK's radioactive waste vitrification programme, which utilises a lithium-sodium borosilicate glass modified with CaO and ZnO to immobilise high level nuclear waste, an investigation was undertaken to evaluate the effects on the structure and chemical durability of altering the CaO to ZnO ratio. Using a 6-component simplified alkali aluminoborosilicate glass, replacement of CaO by ZnO, even in moderate amounts, had a marked effect on the glass structure. Zn K -edge EXAFS identified that Zn existed within two distinct environments, both containing Zn in tetrahedral coordination. At high CaO content, Zn was coordinated in a "hardystonite-like" (Ca2 ZnSi2 O7 ) environment, while higher ZnO content induced destabilization and nano-scale phase separation occurred, forming discrete tri-clusters of Si/Al–O–Zn in a "willemite-like" (Zn2 SiO4 ) environment. The presence of these environments was corroborated by thermal analysis and 29 Si MAS NMR data. Despite this phase separation, glasses with higher ZnO content were found to exhibit the lowest normalized dissolution rates under dilute conditions, as determined using the Single-Pass Flow-Through methodology. Chemical structure analysis indicates that such behaviour is a result of enhanced polymerization of the glass network in the presence of Zn, and a reduced propensity for Si–O–Zn bond hydrolysis in water, resolving a long-running literature debate on the role of Zn on the dissolution of glass in the forward rate. Evidence is presented that indicates the phase-separated regions dissolve at somewhat different rates. These results enhance understanding of CaO : ZnO-containing glass behaviour, important to assess the long-term safety of radioactive waste management and disposal strategies.